Pengaruh Profesionalisme Kerja, Integritas dan Komitmen terhadap Kinerja Pegawai pada Dinas Perhubungan Provinsi Papua Barat - Gunawan, Aloisius Nugroho; Zaini, Zaman (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
Employee Performance can be considered high-quality and accountable if Employees possess Professionalism in their Work, good Integrity, and a high level of Commitment in completing their tasks. This study aims to determine the influence of Work Professionalism, Integrity, and Commitment on Employee Performance at the Department of Transportation in West Papua Province. The respondents in this study consisted of 55 Employees, with data collected using questionnaires. The approach used is quantitative, with Multiple Regression Analysis as the analytical tool. The results of this study are: (1)There is a significant and positive influence of Work Professionalism on Employee Performance at the Department of Transportation in West Papua Province, (2)There is a significant and positive influence of Integrity on Employee Performance at the Department of Transportation in West Papua Province, (3)There is a significant and positive influence of Commitment on Employee Performance at the Department of Transportation in West Papua Province, and (4)There is a significant and positive influence of Work Professionalism, Integrity, and Commitment collectively on Employee Performance at the Department of Transportation in West Papua Province.